Idiopathic intracranial hypertension: evaluation of births and fertility through the hospital episode statistic dataset 2002–2020. Issue 9 (12th August 2022) - Thaller, Mark; Mytton, Jemma; Wakerley, Benjamin; Mollan, Susan; Sinclair, Alexandra
Abstract : Introduction: Idiopathic intracranial hypertension (IIH) predominantly affects women of reproductive age with obesity with a distinct profile of hyperandrogenism and insulin resistance. Polycystic ovary syndrome (PCOS) has an established adverse fertility phenotype that typically affects obese women. IIH may impact reproductive health. Methods: Prospective cohort study of women with IIH aged 18-45 years from the English Hospital Episode Statistic dataset between 1st April 2002 and 31st March 2019. Comparison made to PCOS and general population controls. Main outcome measures were pregnancies, gestational complications, and method of delivery. Results: Data was collected from 17587 IIH, 199633 PCOS, and 10947012 general population patients. The live birth rate, adjusted for age, was significantly lower amongst women with IIH (54.1%) compared to PCOS (67.9%), p<0.0001 and general population (57.7%), p<0.0001. Pre-eclampsia and gestational diabetes risks were higher following a diagnosis of IIH (5.3-fold and 2.7-fold respectively, p<0.0001) compared to general population controls. Following a diagnosis of IIH, elective caesarean section rates were more than twice that of general population (OR 2.4). Conclusions: This data indicates there are lower age-adjusted total pregnancy rates, increased risk of pre-eclampsia and gestational diabetes and a doubling of elective caesarean section rates in those with a diagnosis of IIH.